Determining Timing of Births and Habitat Selection to Identify Lambing Period Habitat for Bighorn Sheep - Robinson, Rusty W.; Smith, Tom S.; Whiting, Jericho C.; Larsen, Randy T.; Shannon, Justin M. (Frontiers in Ecology and Evolution, 2020)
Timing of births in ungulates is influenced by ecological factors, and differences in seasonality of births have evolutionary implications for these mammals. Birthing habitat is one of the most important home-range attributes for ungulates, and disturbances during this time can decrease survival of young and population growth. We calculated timing of births and quantified habitat selected by nursery groups (i.e., females with young) of desert bighorn sheep (Ovis canadensis nelsoni) to produce and project a geographic information system (GIS) model of lambing period habitat (i.e., birthing locations and areas used up to 6 weeks post-parturition) in southeastern Utah, United States. We then applied that model to identify suitable lambing period habitat in an adjacent area for a population of Rocky Mountain bighorn sheep (O. c. canadensis). We monitored 19 global positioning system (GPS) collared females from 2012 to 2013 to delineate the birthing season. We used GPS locations during that time and logistic regression within a model-selection framework to differentiate between lambing period habitat and random locations based on habitat and anthropogenic covariates. We used model coefficients to produce and project a GIS model of lambing period habitat. Across both years, 89% of 45 births occurred in May (range = April 27–June 9). We quantified covariate values at 750 lambing period and 750 random locations during that time in the San Rafael study area. The top model included elevation, slope, terrain ruggedness, aspect, existing vegetation type, and distance to trails and roads. Those variables predicted lambing period habitat for desert bighorn sheep (rho = 0.99, P = 0.02). We then overlaid that model on 1,130 GPS locations from 17 female Rocky Mountain bighorns in the Green River study area. In both areas, a mean of 71% of locations were in the top two (of five) probability categories (San Rafael high = 37%, medium high = 31%; Green River high = 50%, medium high = 23%). Females in lambing period habitat preferred steep, north-facing slopes, rugged terrain, low elevation, and avoided roads. Our GIS model projected areas of lambing period habitat for adjacent desert and Rocky Mountain bighorns and provided land managers with a map of habitat in areas where resource extraction and recreation are increasing. Identifying timing of parturition, and high-probability lambing period habitat, will help managers mitigate temporal and spatial conflicts between bighorn sheep and anthropogenic activities. Similar data regarding timing of births and a GIS model can be applied to conserve habitat for other ungulates also.